Effect of Heat-Loss Boundary on Flame Acceleration and Deflagration-to-Detonation Transition in Narrow Channels. Issue 9 (2nd September 2017) - Wang, Cheng; Zhao, Yongyao; Han, Wenhu
ABSTRACT: The entire process of deflagration-to-detonation transition (DDT) is studied through direct numerical simulations in narrow channels. Calculations with adiabatic and heat-loss boundaries are conducted to investigate the effect of heat loss to walls on flame acceleration and DDT. The numerical results show that heat loss reduces the flame acceleration rate and delays the occurrence of DDT. In the adiabatic channel, flame acceleration is caused mainly by viscosity friction with walls; ultra-fast flame in boundary layers plays a key role in the occurrence of DD. However, in the channel with heat loss the growth of the pressure pulse and the interaction of the leading shock with the boundary layers are weakened. Ultra-fast flame cannot be formed at the boundary layer in front of the flame surface and the occurrence of DDT is attributed to early burning in front of the flame.